Vowel-stemmed NUT participle variation in the Finnish used in the works of Mikael Agricola - Salmi, Heidi; Salmi, Jussi (University of Tartu, 2025)
Finnish had begun to be written in the 16th century, and the language of Mikael Agricola represents the oldest written Finnish. Agricola’s language differs in many ways from contemporary Finnish. This article examines the NUT participle variation found in the Finnish used by Agricola, which no longer exists in the contemporary language.
This study answers whether there are statistically significant variations between NUT participle types caused by linguistic variables. The research shows that phonological variables affect NUT participle variation more than morphological ones. NUT participle variants form an interesting network: variables pair up or group variants so that variables favour a certain variant(s) and alternatively reject other(s).
The overall importance of the variables in selecting a participle was also examined by applying a machine learning classifier algorithm. The most important features in this selection were the stem vowel, if the word has back or front vowels, person and tense.